Effect of thermal radiation and chemical reaction on unsteady MHD plane – Poiseuille flow of fourth-grade fluid in horizontal parallel plates - Joseph, K.M.; Andi, E.A.; Adoyi, E.J.; Akusu, C.O.; Onwubuoua, C. (International Journal of Mathematical Analysis and Modelling, 2024)
A fourth-grade fluid is an important subclass of differential type that is capable of describing shear thinning and shear thickening effects (examples are ketchup, blood, paint, cream, nail polish, etc.). This sort of model is used to explain the flow behaviour of non-Newtonian fluids which are considered vital and applicable in many industrial production processes such as in the drilling of oil and gas wells, polymer extrusion from dye, glass fibre, paper production and draining of plastics films, etc. There is a dearth of knowledge in this area, therefore, this study investigated the thermal radiation and chemical reaction effects on unsteady magnetohydrodynamics plane – poiseuille flow of fourth-grade fluid in horizontal parallel plates channel. The equations that governed the flow were the momentum equation; which is a coupled nonlinear differential equation, the energy equation and concentration equation. The partial differential equations were solved using He – Laplace method which is a combination of Homotopy perturbation method and Laplace transformation method. The findings of the study revealed that: (i) Velocity and temperature fields rise due to the increment of thermal radiation parameter. (ii) For upsurging data of chemical reaction, velocity and concentration fields diminish. (iii) Velocity profile goes up when third and fourth-grade parameters get to raise; Velocity and skin friction fields decline due to the increment of magnetic parameter. (iv) Increasing Prandtl number tend to diminish the velocity and temperature profiles. (v) Strong values of Schmidt number decrease the boundary layer of the Sherwood number field. The results of this work are applicable to industrial processes such polymer extrusion of dye, draining of plastic films etc.